Functional Versatility of AGY Serine Codons in Immunoglobulin Variable Region Genes - Detanico, Thiago; Phillips, Matthew; Wysocki, Lawrence J. (Frontiers in Immunology, 2016)
In systemic autoimmunity, autoantibodies directed against nuclear antigens (Ag) often arise by somatic hypermutation (SHM) that converts AGT and AGC (AGY) Ser codons into Arg codons. This can occur by three different single-base changes. Curiously, AGY Ser codons are far more abundant in complementarity-determining regions (CDRs) of IgV-region genes than expected for random codon use or from species-specific codon frequency data. CDR AGY codons are also more abundant than TCN Ser codons. We show that these trends hold even in cartilaginous fishes. Because AGC is a preferred target for SHM by activation-induced cytidine deaminase (AID), we asked whether the AGY abundance was solely due to a selection pressure to conserve high mutability in CDRs regardless of codon context but found that this was not the case. Instead, AGY triplets were selectively enriched in the Ser codon reading frame. Motivated by reports implicating a functional role for poly/autoreactive specificities in anti-viral antibodies, we also analyzed mutations at AGY in antibodies directed against a number of different viruses, and found that mutations producing Arg codons in anti-viral antibodies were indeed frequent. Unexpectedly, however, we also found that AGY codons mutated often to encode nearly all of the amino acids that are reported to provide the most frequent contacts with antigen (Ag). In many cases, mutations producing codons for these alternative amino acids in anti-viral antibodies were more frequent than those producing Arg codons. Mutations producing each of these key amino acids required only single-base changes in AGY. AGY is the only codon group in which 2/3rds of random mutations generate codons for these key residues. Finally, by directly analyzing x-ray structures of immune complexes from the RCSB protein database, we found that Ag-contact residues generated via somatic hypermutation occurred more often at AGY than at any other codon group. Thus, preservation of AGY codons in antibody genes appears to have been driven by their exceptional functional versatility, despite potential autoreactive consequences.